Preoperative Prediction of a Rare and Highly Aggressive Subtype of Hepatocellular Carcinoma Based on Multimodal Imaging and Clinical Indicators - Chen K; Zhu Y; Liu H; Deng M; Kong W; Wang W (Journal of Hepatocellular Carcinoma, 2025)
Keke Chen,1,* Yuli Zhu,1,* Han Liu,2,* Minying Deng,3 Wentao Kong,4 Wenping Wang1 1Department of Ultrasound, Zhongshan Hospital, Fudan University, Shanghai, 200032, People’s Republic of China; 2Department of Ultrasound, Huashan Hospital, Fudan University, Shanghai, 200040, People’s Republic of China; 3Department of Pathology, Zhongshan Hospital, Fudan University, Shanghai, 200032, People’s Republic of China; 4Department of Ultrasound, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, 210008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wentao Kong, Email breezewen@163.com Wenping Wang, Email puguang61@126.comPurpose: To develop and validate a reliable preoperative non-invasive diagnostic model for dual-phenotype hepatocellular carcinoma (DPHCC) by integrating multimodal imaging and clinical indicators, thereby facilitating clinical decision-making.Patients and Methods: 222 pathologically confirmed patients (61 with DPHCC, 161 with non-DPHCC) were retrospectively enrolled in this study and randomly assigned to training and validation cohorts in an 8:2 ratio. Serological and multimodal imaging characteristics were analyzed. Univariate and multivariate logistic regression analyses identified independent DPHCC predictors and built a nomogram. Model performance and clinical utility were assessed by receiver operating characteristic (ROC) and decision curve analysis (DCA) curve respectively. The calibration curve was used to verify the model. Recurrence-free survival (RFS) was assessed using Kaplan-Meier and Log rank tests.Results: In multivariate analysis, age (OR=0.91; P < 0.001), LDH (OR=1.03; P=0.002), PT (OR=0.14; P < 0.001), AFP (OR=4.04; P=0.019), Adler grade (OR=0.17; P=0.037), non-enhancing area (OR=8.30; P=0.004), arterial phase hyperenhancement (OR=0.12; P=0.015) and enhancing capsule (OR=0.32; P=0.04) were independent predictors of DPHCC. The nomogram achieved a robust predictive performance with C-index (0.92 vs 0.87) and accuracy (0.87 vs 0.86) in the training and validation cohorts. In addition, the calibration curve and DCA also showed good model performance. DPHCC patients had significantly lower RFS than non-DPHCC patients (P = 0.037).Conclusion: A nomogram was established for non-invasive prediction of DPHCC risk utilizing multimodal imaging combined with clinical indicators to help achieve personalized treatment.Keywords: dual-phenotype hepatocellular carcinoma, hepatocellular carcinoma, contrast enhanced magnetic resonance imaging, contrast enhanced ultrasound, combined model, nomogram